Metaizeau Technique for Displaced Radial Neck Fracture Among Children in Erbil, Kurdistan Regional Government, Iraq - Las Jamal Khorsheed; Hasan Ahmed Talat Shareef (Advanced Medical Journal)
Background and objectives: Radial neck fracture if not properly managed can lead to complications including pain and avascular necrosis. The Metaizeau technique of closed intramedullary pinning is a treatment option and it is the aim of this study to assess its outcome. Methods: Metaizeau technique was used in managing radial neck fracture of 21 children at two emergency hospitals in Erbil, Kurdistan Region, Iraq. between July 2018 and September 2019. The postoperative outcome was assessed according to the Metaizeau classification and Mayo performance score to assess the degree of residual angulation as well as for postoperative complications such as joint stiffness.